Evaluation of EN AW-5083 aluminum alloy homogeneity using statistical analysis of mechanical properties - Dolić N.; Brodarac Zovko Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the frame of this investigation, the homogeneity of six (6) ingots of aluminum alloy EN AW-5083 cast by semi-continuous vertical Direct Chill casting (DC) Process was investigated correlating mechanical properties in as-cast and homogenized condition. The investigation followed the static design of the Latin square. Determination of the ultimate tensile strength and elongation across the cross-sectioned sliced at the ingots’ fronts and rears in as-cast state revealed differences per cross section of each particular slice. Comparison of obtained differences enabled evaluation of mechanical properties homogeneity of the ingots as a whole. The influence and significance of homogenization was also quantified correlating the mechanical properties results for as-cast and homogenized state at the front and rear position in ingot. The results were processed using the StatSoft® STATISTICA 13.2 software package using charge, slice height and slice width as sources of variability. Comparison of obtained statistical results for both states respectively in respect to the sampling position enabled estimation of homogenization process influence on mechanical properties.